State and Perspectives of Development of the European Space of Education and Science: the System of Scientific Knowledge for a Period of Life - RIDEI NАTALIIA; BOGUTSKII, IURII; SHOLUDIAK, ANASTASIIA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2018)
The article deals with the stages of formation of the European space of education and science, in particular, the key role of each international assembly is determined for 20 years. Structuralorganizational and structural-functional analysis of the effectiveness of the legislative and structural implementation of higher education systems for the development of the Bologna process was conducted, as well as a chronological analysis of the forums held under the auspices of the Bologna Process.